Causal Relationship Between Housing Policies implemented since late 1990s and Real Estate Bubble in China - Faltus, Jakub; Taušer, Josef; de Batz de Trenquelléon, Laure Sabine Marie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the causal relationship between housing policies implemented since the late 1990s and the formation of a real estate bubble in China. Through a mixed approach combining trend development and regression analyses, the research investigates how fiscal and urban/land policies have influenced real estate prices and market dynamics. The thesis aims to verify whether fiscal and urban/land policies correlate with price fluctuations while controlling for other statistically significant factors, such as GDP growth. The study also checks for policy contradictions and unintended consequences contributing to market instability. The research sheds light on complex interactions between policy interventions and broader economic forces contributing to China's real estate bubble.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses